Literatur Review; Pengaruh Pemberian Olahan Ikan Gabus Terhadap Proses Penyembuhan Luka DM - Avita Intan Safitri; Qori'ilah Saidah; Ceria Nurhayati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Introduction: Diabetes mellitus wound is one of the complications where there is a wound that is experienced by people with diabetes mellitus with a long prognosis and poor control of blood sugar levels. This study aims to identify the effectiveness of snakehead fish gourd (Channa Striata) on wound healing of diabetes mellitus with a regular consumption range. Method: This study uses a Literature Review research method The systematic review searched six bases of electronic data (Google Scholar, Scopus, PubMed, Science Direct, CINAHL, and ProQuest) for previous studies using cross-sectional designs published between 2015-2020. Analysis: With various processed processes, snakehead fish tend to have benefits and ingredients in the wound healing process with a sustainable consumption period. Result: The results obtained 10 journals and articles that meet the inclusion and exclusion criteria according to the research topic. The results showed that snakehead fish with a high protein content has the potential not only to improve healing in diabetes mellitus wounds but also improve nutritional status and hypoalbumin improvement.Keywords: Fish Cork (Channa Striata); Diabetes Mellitus Wounds; Wound Healing; AlbuminÂ